Hubungan Dukungan Keluarga Dengan Kepatuhan Kontrol Pengobatan Pada Pasien Hipertensi Di Poli Penyakit Dalam Rumah Sakit AMC - Sari, Ria; Istianah, Istianah; Sutisna, M. Iqbal; Kusmiran, Eny (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify the relationship between family support and medication adherence in hypertensive patients at the Internal Medicine Department of AMC Hospital. The research method used is a correlational design with a cross-sectional approach, involving 61 respondents undergoing hypertension treatment. The results show that 41% of respondents have inadequate family support, and 54.1% are non-adherent to medication control. Analysis using Chi-Square test produced a p-value of <0.001, indicating a significant relationship between family support and adherence. Good family support positively influences patients' adherence to therapy, highlighting the importance of enhancing family involvement in the treatment process to prevent further complications.